Method of forming requirements to the ballistic coefficient of the kinetic weapon throwing element - Біленко, Олександр Іванович (Eastern-European Journal of Enterprise Technologies, 2013)
The article deals with the influence of ballistic coefficient of the throuring element on the characteristics of the kinetic non-lethal and deadly weapons with limited hit probability range. It is defined that the range of kinetic weapons employment greatly depends on the ballistic coefficient of the throuring element, that’s why there is the necessity in methods to calculate permissible ballistic coefficient. Designing deadly weapons with limited hit probability range is considered one of the most complicated, because of the simultaneous accomplishment of reliable hit probability requirements at ranges close to accurate inclusive. The method that permits to form requirements to ballistic coefficient of the throuring element of kinetic non-lethal and deadly weapons with limited hit probability range is developed.